Students’ Perception of Synchronous Learning of Writing Through Zoom Chat Respond - Wahyunengsih, Wahyunengsih (IJET (Indonesian Journal of English Teaching), 2024)
Zoom Cloud is definitely one of the major tools of distance learning during 2019 until now. Writing is a course that need direct feedback of the students work. The objectives of the study are finding the students’ perception of writing course 2 of learning writing through zoom chat respond. Zoom Chat is a feature provided by the application, but mostly has not been used for more valuable learning tools. This present study uses qualitative research that describes the data from the questionnaire and interview. The participants were 25 students of class 4B English Education Department UIN Syarif Hidayatullah Jakarta. The result of the study shows that using Zoom chat respond can stimulate students to get motivated in answering the questions because their writings are directly read by lecturers and other friends.